Study of a Highly Effective and Affordable Highway Interchange - ITL Interchange - JovanoviÄ‡, Goran; AtelÅ¡ek, Rafko (Salehan Institute of Higher Education, 2020)
In this paper we present a new solution for the highway interchange, which represents the best compromise between the traffic capacity, the land area used and construction cost. The difference between the known and the new design solution is in the implementation of the opposite directional ramps which are widely separated in the area of the interchange. In the middle, between the directional ramps, some space is created for the left directional ramps. Interchange should be used for four-way highway interchanges or other heavy traffic roads junction in order to increase the capacity and traffic safety at the crossing point. It has no conflict points. ITL Interchange left directional ramps is much shorter than all other known solutions for interchanges. The interchange is built in two levels. These two facts significantly lower the cost of construction. The study compares different types of interchanges. We made a geometric comparison and performance measures. In geometric comparison, the greatest advantages of the ITL interchange are the shortest overall roadway length and the shortest overpasses length. Therefore, such an interchange is advantageous in terms of construction and maintenance costs. When measuring performance, ITL Interchange achieves the best results regardless of the number of vehicles.